Workers' view on the preventive needs for civilization diseases' in prophylactic care taken on employees - Agnieszka Lipińska-Ojrzanowska; Jadwiga Magnuska; Dominika Świerczyńska-Machura; Jolanta Walusiak-Skorupa; Andrzej Marcinkiewicz; Marta Wiszniewska (Nofer Institute of Occupational Medicine, 2019)
Background Every year in Poland almost 5 million prophylactic examinations (PEs) are carried out by occupational medicine specialists (OMPs) among workers, for the purposes envisaged in the Polish Labour Code. The aim of this study was to collect workers' opinions on the possible extension of these check-ups in the field of prophylaxis and prevention of civilization diseases (CivDs), focusing also on the "healthy lifestyle" recommendations. Material and Methods The study group comprised 325 employees who filled out an anonymous questionnaire containing questions about the possible extension of the PE scope for CivD and cancer prophylaxis. During medical check-ups, evaluation of the incidental glucose (IG) and total cholesterol (TCh) levels, waist circumference measurement and electrocardiography (ECG) were proposed. The respondents were asked about the most interesting issues for discussing with OMPs. Results Screening tests for some cancers (69.5%) and risk factors for CivDs (61.5%) were indicated as the most interesting topics to discuss with OMPs. The possibility for evaluating the levels of IG and TCh during PEs was approved by approx. 94.8% and 95.3% of the respondents, respectively. Almost 96% accepted having ECG and 80% agreed to waist circumference measurement. As many as 89.5% of the respondents supported the idea of organizing physical activities at their workplaces, and 77.8% were eager to learn about "healthy lifestyles" during training sessions conducted at their workplaces. Conclusions Restricting the aim of PEs just to certifying the ability to work, or identifying certain medical contraindications, means losing a chance for implementing the prophylaxis and prevention of diseases' development among active working subjects. The kinds of activities proposed by the authors of this publication have been approved by the employees. Med Pr. 2019;70(4):425-33